Statistics performance of elementary and middle school students in the context of D-Estat - Cazorla, Irene Maurício; Utsumi, Miriam Cardoso; Santana, Eurivalda Ribeiro dos Santos (Universidade Estadual de Campinas, 2020)
We analyzed the statistical performance of 1,305 students from 1st to 9th grade, in elementary and middle schools, in four public schools in the state of Bahia-Brazil, in the context of a collaborative university-school research (D-Estat). We built three instruments, according to the education level, from which we analyzed three issues involving qualitative, discrete and continuous variables; conversion of native language data to bar graphs; reading of frequency distribution and two-way tables; calculation of mean, median and mode. The main results show that performance falls substantially from one level to another, but within each school grade there is a growing trend, greater in Elementary School, signaling stagnation in the Middle School. The results indicate the need to elaborate teaching sequences validated in the reality of the schools, which allow the active role of students, in the learning processes and, consequently, for statistical literacy.